Minding less: Exploring mindfulness and mindlessness in organizations through Skillful Means. Issue 5 (November 2018) - Vu, Mai Chi; Wolfgramm, Rachel; Spiller, Chellie
Mindfulness has received increased attention in organizational studies. Yet we ask, is mindfulness necessary, indeed achievable, in every "moment" and every context? Mindfulness as co-opted by organizations is often considered a positive and helpful state, while little attention is paid to the important notion of mindlessness. Our comprehensive exploratory review of mindfulness and mindlessness highlights theoretical debates and responds to calls for a more balanced approach to mindlessness and mindfulness. In addition, it highlights practical implications to management learning by introducing Eastern Buddhist principles of non-attachment, practiced through the key concept of Skillful Means. A distinctive contribution of this article is a Five-Fold Framework detailing five aspects of a skillful mindful and mindless approach: context-flexibility, managerial emotional display, managerial learning under complex situations and dilemmas, transferring mindfulness practices from individual to organizational level, and context-sensitive research.